2019
DOI: 10.1038/s41598-019-44520-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel lactic acid bacteria strains as inoculants on alfalfa silage fermentation

Abstract: The effects of new strains of lactic acid bacteria on alfalfa silage fermentation were evaluated. The experiment was performed using a completely randomized design (with three replicates) based on a 6 × 6 factorial assay with 6 inoculants (I): Control (CTRL), Commercial inoculant (CI), Lactobacillus pentosus 14.7SE (LPE), Lactobacillus plantarum 3.7E (LP), Pediococcus pentosaceus 14.15SE (PP), and Lactobacillus plantarum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
0
22
2
2
Order By: Relevance
“…L. pentosus was exclusively identified in oat silage at 10 °C, 15 °C, and 25 °C, and became to be the most abundant species at 10 °C after 60 days of ensiling. Agarussi et al have performed the trail of inoculating silage with L. pentosus , and the results showed that it had strong ability of producing lactic acid and reducing pH [ 31 ]. According, L. pentosus might be an interesting species for the development of LAB inoculants for cold climates.…”
Section: Resultsmentioning
confidence: 99%
“…L. pentosus was exclusively identified in oat silage at 10 °C, 15 °C, and 25 °C, and became to be the most abundant species at 10 °C after 60 days of ensiling. Agarussi et al have performed the trail of inoculating silage with L. pentosus , and the results showed that it had strong ability of producing lactic acid and reducing pH [ 31 ]. According, L. pentosus might be an interesting species for the development of LAB inoculants for cold climates.…”
Section: Resultsmentioning
confidence: 99%
“…The fast increase in LAB counts frequently observed in inoculated silages in early fermentation indicates that LAB strains are competitive among the epiphytic communities. Moreover, the reduction in the LAB population after this initial peak is expected because low pH and lack of fermentable substrates result in bacterial death (Xu et al ., 2017; Nascimento Agarussi et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…LAB population in forage samples are very less, it's not sufficient to initiate the fermentation rapidly and also unable to produce a higher concentration of lactic acid during fermentation, this condition could favor the growth of clostridia and causes deterioration of silage quality [38]. Many reports claimed that an addition of L. plantarum, L. pentosus, and Pediococcus pentosaceus effectively ferment the different types of grass and legume plants and preserve its life for a long time [39][40][41]. Therefore, the addition of LAB is essential criterion for enhancing the fermentation process and rapidly decreased the pH of the silage by producing a higher amount of lactic acid with a lesser extent to acetic acid.…”
Section: Discussionmentioning
confidence: 99%